2022
DOI: 10.1155/2022/7851562
|View full text |Cite
|
Sign up to set email alerts
|

Crack Detection Method of Sleeper Based on Cascade Convolutional Neural Network

Abstract: This work presents a new method for sleeper crack identification based on cascade convolutional neural network (CNN) to address the problem of low efficiency and poor accuracy in the traditional detection method of sleeper crack identification. The proposed algorithm mainly includes improved You Only Look Once version 3 (YOLOv3) and the crack recognition network, where the crack recognition network includes two modules, the crack encoder-decoder network (CEDNet) and the crack residual refinement network (CRRNe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Deep learning [14][15][16][17][18] has recently been successful in the image recognition and target detection fields. Universally, scholars apply deep learning to achieve ultrasonic Lamb wave imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning [14][15][16][17][18] has recently been successful in the image recognition and target detection fields. Universally, scholars apply deep learning to achieve ultrasonic Lamb wave imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Cha et al [12] and Eisenbach et al [13] also performed patch-based classification, which can only identify the presence or absence of cracks in a corresponding image patch. Researchers also utilized another deep learning scheme called object detection for localizing the cracks, along with identifying them in an image [14,15]. However, these models can only classify and localize the cracks in a concrete structure instead of detecting cracks at a pixel level.…”
Section: Introductionmentioning
confidence: 99%
“…Y Zhang et al [ 7 ] used the YOLO v3 algorithm as a base and was able to detect the cracks efficiently by using MobileNet for transfer learning and the convolutional block attention model. The authors of [ 8 ] carried out research on various CNN-based algorithms, and found that MobileNet yielded the best accuracy for a masonry dataset. J. K. Chow et al [ 9 ] carried out crack detection on concrete images using a convolutional autoencoder and decoders.…”
Section: Introductionmentioning
confidence: 99%